2020
DOI: 10.1007/s00420-020-01525-6
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability as a measure of mental stress in surgery: a systematic review

Abstract: Purpose There is increasing interest in the use of heart rate variability (HRV) as an objective measurement of mental stress in the surgical setting. To identify areas of improvement, the aim of our study was to review current use of HRV measurements in the surgical setting, evaluate the different methods used for the analysis of HRV, and to assess whether HRV is being measured correctly. Methods A systematic review was performed according to the Preferred Reporting Items for Systematic reviews and Meta-Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 32 publications
1
32
2
Order By: Relevance
“…Although reporting bias cannot be entirely ruled out, the SURG-TLX follows the trend of objective parameters like salivary cortisol levels [43]. HRV seems to be an adequate method to assess mental surgical stress as well [44]. While heart rate was statistically significantly higher (within subject difference 1.0 bpm, p = 0.046) and HRV lower (within subject difference − 2.5, p = 0.015) in the music group, the absolute difference observed cannot be considered clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although reporting bias cannot be entirely ruled out, the SURG-TLX follows the trend of objective parameters like salivary cortisol levels [43]. HRV seems to be an adequate method to assess mental surgical stress as well [44]. While heart rate was statistically significantly higher (within subject difference 1.0 bpm, p = 0.046) and HRV lower (within subject difference − 2.5, p = 0.015) in the music group, the absolute difference observed cannot be considered clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Music did significantly reduce mental workload and several previously identified key stressors of surgery, and its use in the operating theater is reportedly viewed favorably. Higher perceived stress is associated with a decreased HRV even throughout the night, indicative of a protracted recovery time [44]. As music can attenuate the stress response to surgery in patients undergoing surgery, future research should incorporate its effect on mental workload through HRV with attention to recovery from surgical task performance as well.…”
Section: Discussionmentioning
confidence: 99%
“…HRV is also used to study stress levels of surgeons during operations. The review by The et al shows that there are significantly more studies on this topic ( n = 17) [ 17 ]. For example, reviews showed that stressed surgeons (e.g., intraoperatively) offered reduced HRV [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of heart rate variability (HRV) is a possible method for objective monitoring of workload [ 15 ]. HRV is often used for stress identification in surgeons [ 16 , 17 ]. The HRV is defined as variations in time between consecutive heart beats and it’s a very sensitive indicator for dysregulation of the autonomic nervous system (ANS) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate variability (HRV) is a measure of the variation in time between adjacent heartbeats, otherwise known as R-R intervals [ 1 , 2 ]. HRV is a powerful biomarker and is sensitive to the level of activity and work, of both physiological and psychological systems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%